HAX1, gene responsible for Kostmann syndrome, regulates gingival epithelial barrier function via intracellular trafficking of JAM1 - Tanigaki, Keita; Tamamori, Tsukasa; Sasaki, Naoko; Matsumura, Risako; Yamaga, Shunsuke; Sakanaka, Akito; Amano, Atsuo; Matsusaki, Michiya; Takeuchi, Hiroki; Kuboniwa, Masae (Frontiers in Cell and Developmental Biology, 2025)
BackgroundKostmann syndrome is an autosomal recessive disorder caused by a mutation of the hematopoietic cell-specific Lyn substrate 1 associated protein X-1 (HAX1) gene, and characterized by low number of neutrophils and increased susceptibility to infections. Additionally, Kostmann syndrome is known to be complicated by periodontitis, though the etiological molecular basis remains unclear. We previously reported findings showing that junctional adhesion molecule 1 (JAM1), a tight junction-associated protein, has an important role to maintain epithelial barrier function in gingival tissues, which prevents penetration of bacterial virulence factors, such as lipopolysaccharide (LPS) and peptidoglycan (PGN). In the present study, the effects of HAX1 on gingival barrier function were investigated.ResultsExaminations of immortalized human gingival epithelial (IHGE) cells showed HAX1 localization in mitochondria. In HAX1-knockdown IHGE cells, significantly decreased levels of JAM1 were found. Additionally, cisplatin, a chemotherapeutic agent reported to inhibit HAX1, also led to decreased expression of both HAX1 and JAM1. Furthermore, JAM1 was scarcely detected in HAX1-knockout cells, while administration of bafilomycin A1, a lysosomal inhibitor, restored JAM1 expression in those cells. Finally, using a three-dimensional multilayered gingival epithelial tissue model, HAX1 knockout along with cisplatin administration was also found to increase permeability to LPS and PGN, which was dependent on JAM1 expression.ConclusionThese results indicate that periodontal diseases complicated with Kostmann syndrome are induced by reduced JAM1 expression, caused by JAM1 being missorted into lysosomes by HAX1 dysfunction.